A Silanol-Based Nanocomposite Coating for Protection of Aa-2024 Aluminium Alloy - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Melo-Hurtado, F; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Azocar-Guzman, M; Azocar-Guzman, M; Gonzalez-Sanchez, E; Gonzalez-Sanchez, E (2011)
Sin Editorial Disponible